BENTUK KONTRIBUSI DAYA TARIK WISATA MONKEY FOREST DALAM MENSEJAHTERAKAN MASYARAKAT LOKAL DI DESA PADANG TEGAL KECAMATAN UBUD - I Wayan Restu Suarmana; I Gusti Agung Oka Mahagangga (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2014)
Abstrack The tourist destination of Wanara Wana or better known as the Monkey Forest is a tourist destination which is very famous in Ubud especially in the traditional village of Padang Tegal. Existence Tourist destination of Monkey Forest provide a huge influence for the welfare of the local communities in the traditional village of Padang Tegal. It is seen from the contributions that the Monkey Forest gave to the traditional village of Padang Tegal. That was my Assumptions to choose this research topic